Acerca de los antecedentes ockhamianos del contractualismo británico moderno y del neocontractualismo contemporáneo - Fraga, Fernando Aranda (Veritas)
“Contractualism” is understood as the theory by which the society’s foundation and possibility is explained and justified starting from a covenant between its members, models which was fully developed during the Modern Ages. The secularization of society – which had already began to develop during the Middle Ages – and a atomist conception of society were the motives which conditioned the appearance of this social theory during the Modern Ages. Tracing the origins of this doctrine, the sophists’ incipient development can be mentioned; who despite Plato’s criticism, proposed the establishment of social covenants in order to avoid injustice and damages among individuals. Thus among the sophists arose the idea that justice is a covenant, a convention between men, lacking absolute value in itself. Other theorists of law and the State, like Michael Villey, stress the role of William the Ockham as regards this covenant. In this sense it is possible to assert that on modern contractualism, not wholly political influences are perceived, coming from the nominalist current founded by Ockham. In the first part, those possible theoretical influences about the Master of Oxford will be analized. Ockham produces a radical subversion in the Classic and the Ancient World. The power he liberated could not be fully reabsorbed by his own system. On the contrary, it originated a plurality of trends which kept developing in the course of Modernity. On the anthropologist field, this thought about the earthly and singular made subjectivity and the individual to be in the limelight, from where it comes Ockham’s supposed germs of modern liberalism. Humanism will be the direct heir of nominalist thought. It is remarkable the way – particularly in British spirit – this notion of constructivist and conventionalist preparation of concepts permeated This leads to Ockham’s assertion that there are no good or bad things in themselves, but just as they relate to the positive decrees of the divine will. The consequences of such thought were not assumed by Ockham, who kept alive his faith in God and his Revelation, though, obviously enough, just a small step by other thinkers less connected to religious objections was needed to – by virtue of nominalists principles – reach immanentist positions which began to burst as Modernity went on. In the moral field this would give rise to the establishment of a sense of ethics which is acquired by modern conscience stemming from the perception of social habits. Property, for instance, appears after the edenic breaking-off as a result of the original sin. From then on it will have to be regulated. To all this, it should be added Ockham’s own conception about the origin of political power, which he places in hands of every individual, who receives it from God to then reach an agreement with the other individuals in order to hand over their rights in behalf of someone who will rule over them. Thus a conventional sense of moral and justice keeps being formed